Heidegger's metaphysics the overturning of 'Being and time' - Daly, Aengus (Bloomsbury Academic, 2024)
"Heidegger and Metaphysics explores how Heidegger continued the project of Being and Time, developing a new kind of metaphysics through a critique of Kantian transcendental philosophy. Drawing on Heidegger's published and unpublished work in the late 1920s, including lecture courses, drafts, and correspondence, it reconstructs the philosophical and phenomenological justification for this project, its implications for Heidegger's phenomenology of time, his account of philosophical concept formation, and his relationship to transcendental philosophy"--
Keywords: Heidegger, Martin -- 1889-1976; Heidegger, Martin; Metaphysics; Transzendentalphilosophie; Metaphysik